Developing Students’ Multicultural Background in Structure Courses - Haryanti, Sri; Setyandari, Ana (International Journal of Active Learning, 2019)
In applying English sentence structure, learners need to know the patterns that must be mastered. In addition, in making sentences learners need to pay attention to different cultures between one learner and another. This study discusses the background of students? various cultures. This diversity is in terms of regional origin or provinces, mastered languages, and hobbies. However, this study focuses on hobbies. Student hobbies include: reading books, reading novels / comics, writing novels, graphic design, drawing, and so on. This is what encourages researchers to know the benefits of hobbies in learning English sentence structure. In this study researchers propose the problem "How to develop students? multi-cultural background in ?Structure? courses?? This problem is solved by collecting data on the construction of sentences that allude to multi-culture; thus they are referred to as data sources which were then scrutinized and recorded. In theory this method is called by Sudaryanto observation method. Finally, the research data were analyzed by qualitative descriptive method proposed by Seliger and Shohamy. From the results of the analysis, it can be known the kinds of construction that includes the students? hobbies. What researchers did was asking students to allude their hobbies in practicing the English structures. This appeal was initially ignored by students. Only a small number of students alluded their hobbies in making sentences. Researchers urged again to consider their hobbies in making sentences. In the end most students (75%) pay attention to hobbies or remember their hobbies in applying an English sentence.